2015
DOI: 10.1002/adsc.201500205
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Synthesis of (S)‐3‐Hydroxyisobutyric Acid from Glucose usingPseudomonas taiwanensisVLB120 B83 T7 Catalytic Biofilms

Abstract: Thec hiral building block (S)-3-hydroxyisobutyric acid [(S)-3-HIBA] was produced either by conversion of isobutyric acid or directly from glucose utilizing cells of Pseudomonas taiwanensis VLB120 B83 T7 as catalysts.T his strain carriesapoint mutation in the gene encoding 3-hydroxyisobutyrate dehydrogenase (mmsB), leading to its inactivation.T he maximal specific activity in resting-cell biotransformations using isobutyric acid as substrate was 4.9 AE 0.4 Ug cdw À1 .O verexpression of the 2-ketoisovalerate pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…We have identified isobutyrate as one of the interesting chemicals that are to be produced through chain elongation. Isobutyrate, though not a MCFA, is a useful platform chemical that can be used as a precursor for: (1) methyl methacrylic acid (MMA), which is used for production of transparent thermoplastics with an annual market size of up to 2.2 million tonnes; (2) sucrose acetate isobutyrate, which is used as an emulsifier in many commodities with an annual market size of up to 100 000 tonnes; or (3) 3‐hydroxyisobutyric acid that can be used for synthesis of vitamins, antibiotics and many other bioactive compounds . A recent study also showed that isobutyrate could be biologically reduced in a syngas fermentation process to yield isobutanol, a commercially applied fuel substitute that has a superior performance over ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…We have identified isobutyrate as one of the interesting chemicals that are to be produced through chain elongation. Isobutyrate, though not a MCFA, is a useful platform chemical that can be used as a precursor for: (1) methyl methacrylic acid (MMA), which is used for production of transparent thermoplastics with an annual market size of up to 2.2 million tonnes; (2) sucrose acetate isobutyrate, which is used as an emulsifier in many commodities with an annual market size of up to 100 000 tonnes; or (3) 3‐hydroxyisobutyric acid that can be used for synthesis of vitamins, antibiotics and many other bioactive compounds . A recent study also showed that isobutyrate could be biologically reduced in a syngas fermentation process to yield isobutanol, a commercially applied fuel substitute that has a superior performance over ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, P. putida GS1 is superior in terms of resilience to both limonene and perillic acid as compared to P. taiwanensis VLB120. Nevertheless, P. taiwanensis VLB120 is a well‐characterized biofilm producer and process parameters have been described for the biofilm‐based production of toxic compounds such as ( S )‐styrene oxide (Gross et al, ; Halan et al, ), octanol (Gross et al, ), and ( S )‐3‐hydroxyisobutyric acid (Lang et al, ). Hence, P. taiwanensis VLB120 was still included as a potential production strain for perillic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Gut microbiota productions can be absorbed by the colonic epithelium; they enter the bloodstream and play an important role in regulating the metabolism of glucose, fatty acids, and cholesterol. Changes in serum metabolite levels in CeD have been identified and suggest significant changes in the gut microbiota of CeD subjects [60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%